CHILDFREE DALAM PERNIKAHAN ‎DITINJAU DARI SURAH AN-NAHL AYAT 72 ‎‎(ANALISIS TERHADAP TAFSIR AL ‎MARAGHI)‎ - Sundari, Ayun (Jurnal Ushuluddin, 2022)
This research is motivated by the issue of the decisions made by couples who consciously and voluntarily choose not to have children or do not desire to have children in the future, whether biological, stepchildren, or adopted. As a society that believes children are a blessing, this is a surprising decision for others in the community. This society is faced with the inability to have children due to physical health issues of one of the spouses or the innate instinct present in every human being when confronted with children, which often leads to behaviors that make adulthood a source of comfort or a calming remedy. The purpose of this research is to analyze and provide an understanding of the meaning of childfree in marriage according to Al-Maraghi. The findings of this research show that when childfree is associated with Surah An-Nahl, verse 72, it becomes evident that this concept is quite the opposite. It is understood that if the decision to be childfree is based on personal pleasure without a solid foundation, solutions and alternatives can be sought. This is different from the case of postponing pregnancy, either by using contraception or naturally, without terminating the pregnancy.